2013
DOI: 10.1021/jp4027942
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Mössbauer Characterization, and Ab Initio Modeling of Iron Oxide Nanoparticles of Medical Interest Functionalized by Dopamine

Abstract: Polyol made from about 10 nm sized maghemite nanoparticles was functionalized by a hydrophilic catechol derivative, namely, dopamine. Infrared spectroscopy confirmed the grafting, whereas X-ray diffraction and transmission electron microscopy did not show either structural or microstructural change on the iron oxide particles. 57Fe Mössbauer spectrometry allowed, giving a quantitative assessment of the bonding preferences of dopamine on the iron oxide surfaces, the π-donor character of this ligand to be exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…[37 To corroborate the XPS results, 57 Fe Mçssbauer spectrometry was performed as a useful technique for determining the oxidation state of Fe species. [38] The Mçssbauer spectra recorded at 300 and 77 K on the bare magnetic NPs are illustrated in Figure 5. The spectrum at 300 K exhibits a hyperfine complex structure consisting of a magnetic sextet with broadened lines and a central quadrupolar doublet: these two components are attributed to the larger and the smaller nanoparticles, which exhibit slower and faster superparamagnetic relaxation phenomena, respectively.…”
mentioning
confidence: 99%
“…[37 To corroborate the XPS results, 57 Fe Mçssbauer spectrometry was performed as a useful technique for determining the oxidation state of Fe species. [38] The Mçssbauer spectra recorded at 300 and 77 K on the bare magnetic NPs are illustrated in Figure 5. The spectrum at 300 K exhibits a hyperfine complex structure consisting of a magnetic sextet with broadened lines and a central quadrupolar doublet: these two components are attributed to the larger and the smaller nanoparticles, which exhibit slower and faster superparamagnetic relaxation phenomena, respectively.…”
mentioning
confidence: 99%
“…A catechol ligand bearing an amino group, also known as dopamine (DA), was grafted onto the surface of the particles to make them repulsive and slightly positively charged in physiological pH conditions (Figure ). A specific protocol was developed, adapted from an already established one (Basti et al, ; Fouineau et al, ) to attach the required amount of DA at the surface of the NPs, favoring weak yet nonzero clustering. The idea was to form small controlled aggregates of less than 100 nm in hydrodynamic diameter to improve the total relaxivity of the particles without furtherly limiting their circulation time inside the blood vessels, when administrated intravenously.…”
Section: Resultsmentioning
confidence: 99%
“… The chemical composition of the polyol‐made and water washed maghemite nanoparticles (dark red color) changed during dopamine (DA) grafting to become closer to that of magnetite (black color). Indeed, thanks to the Pi donor properties of DA, a non‐negligible charge density is transferred from DA to the ferric surface cations, during the complexation reaction (Fouineau et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The experimental results demonstrate that catechol and bisphosphonate molecules can be exchanged and that the ligand exchange increases by using a large excess of bisphosphonate and sonication. J. Fouineau et al demonstrated that the DFT simulations could be used to elucidate the electronic transfer and the binding mode between coating ligands of biological interest and the SPIONs surface [66]. In particular, the authors investigated γ-Fe2O3 nanoparticles functionalized with dopamine, and the calculations were performed with the PBE functional.…”
Section: Experimental Results Of S Kumar Et Al Show a Different Stamentioning
confidence: 99%